General practitioners’ and students’ experiences with feedback during a six-week clerkship in general practice: a qualitative study - Gran, Sarah Frandsen (Scand J Prim Health Care, 2016)
OBJECTIVE: Feedback may be scarce and unsystematic during students' clerkship periods. We wanted to explore general practitioners' (GPs) and medical students' experiences with giving and receiving supervision and feedback during a clerkship in general practice, with a focus on their experiences with using a structured tool (StudentPEP) to facilitate feedback and supervision. DESIGN: Qualitative study. SETTING: Teachers and students from a six-week clerkship in general practice for fifth year medical students were interviewed in two student and two teacher focus groups. SUBJECTS: 21 GPs and nine medical students. RESULTS: We found that GPs first supported students' development in the familiarization phase by exploring the students' expectations and competency level. When mutual trust had been established through the familiarization phase GPs encouraged students to conduct their own consultations while being available for supervision and feedback. Both students and GPs emphasized that good feedback promoting students' professional development was timely, constructive, supportive, and focused on ways to improve. Among the challenges GPs mentioned were giving feedback on behavioral issues such as body language and insensitive use of electronic devices during consultations or if the student was very insecure, passive, and reluctant to take action or lacked social or language skills. While some GPs experienced StudentPEP as time-consuming and unnecessary, others argued that the tool promoted feedback and learning through mandatory observations and structured questions. CONCLUSION: KEY POINTS: Observing the teacher and being supervised are essential components of Medical students' learning during general practice clerkships. Teachers and students build mutual trust in the familiarization phase. Good feedback is based on observations, is timely, encouraging, and instructive. StudentPEP may create an arena for structured feedback and reflection.